First Report of Cercospora chevalieri Causing A Leaf Spot Disease on Amorphophallus konjac in China - Chu, Honglong; Dong, Kun; Gao, Yong; Liu, Zhao; Huang, Jie; Zhang, Yanan (Plant disease, 2024)
Amorphophallus konjac, commonly called voodoo lily, is a cash crop widely cultivated in southwest China (Gao et al. 2022). In August 2022, leaf spot symptoms were observed in a field (1 ha) located at Fuyuan (25.67°N; 104.25°E), Yunnan, China, resulting in substantial economic losses. Brown lesions, with an incidence ranging from 20 to 40%, typically had a whitish or gray center and were surrounded by yellow halos. Microscopic observations of the spots revealed anamorphic species Cercospora chevalieri. Conidiophores were 50-150 × 4-7 μm, cylindrical, unbranched, smooth-walled, pale brown and aggregated in dense fascicles arising from a brown stroma. The conidiogenous cells were integrated, terminal or intercalary, pale brown to brown and proliferated sympodially. The conidiogenous loci were thickened and darkened, and 2-3 μm in diam. The conidia were formed singly, obclavate-cylindrical, 90-160 × 5-7 μm, with an average of 130 × 6 μm (n = 30), 6-11 septa, thin-walled, smooth, hyaline or subhyaline, straight or curved with an obtuse apex and obconically truncate base, with thickened and darkened hilum. These morphological characteristics matched those of C. chevalieri, the causal agent of leaf spot on A. paeoniifolius (Braun et al. 2014; Saccardo et al. 1913). A conidial suspension in sterile water from lesions was used to inoculate water agar, and germinated conidia were transferred to potato dextrose agar（PDA) and incubated at 27°C for 7 days. Induction of sporulation was unsuccessful using PDA, as well as malt extract agar, potato sucrose agar and synthetic nutrient-poor agar. Two out of ten isolates were selected for molecular identification and pathogenicity assay. Genomic DNA from two pure isolates (KUNCC22-12536 and KUNCC22-12537) was extracted for PCR and amplified with primers for the internal transcribed spacers (ITS: ITS1/ITS4), calmodulin (CMD: CAL228F/CAL2Rd), translation elongation factor 1-alpha (TEF1-α: 728F/986R), actin (ACT: 512F/783R), histone H3 (HIS3: CYLH3F/CYLH3R), beta-tubulin gene (TUB2: BT-1F/BT-1R) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH: Gpd1/Gpd2), respectively (Vaghefi et al. 2021). The newly generated sequences for ITS (OP719153/OP719154), CMD(OP740904/OP740905), TEF1-α (OP740910/OP740911), ACT (OP740902/OP740903), HIS3 (OP740908/OP740909), TUB2 (OP740912/OP740913), GAPDH (OP740906/OP740907) of C. chevalieri were submitted to GenBank. So far, no sequence data of C. chevalieri were available in the GenBank database. As expected, most genes (TEF1-α, ACT, CMD, HIS, TUB2 and GAPDH) showed 91 to 95% identity to their best hits within species of the genus Cercospora. The phylogenetic tree showed that sequences retrieved from two isolates obtained from the A. konjac leaf spots clustered together within Cercospora forming a strongly supported clade. To test Koch's postulates, ten four-month-old healthy A. konjac plants grown in pots were used for a pathogenicity test in a greenhouse. One leaf of each plant was inoculated with mycelial plugs, and one leaf was inoculated with a sterile PDA plug. These plants were enclosed in plastic bags for 72 h. Only leaves inoculated with mycelium plugs produced brown lesions, which appeared after 10 to 14 days on inoculated leaves. Control plants treated with sterile PDA plugs remained asymptomatic. This experiment was repeated twice with the same results. C. chevalieri was reisolated from infected leaves and identified based on morphology and Sanger sequencing of the ITS region. To our knowledge, this is the first report of C. chevalieri causing leaf spot on A. konjac and the first report of this species from China (Braun et al. 2014), which provides key information for diagnosis and management of this disease.